Sosialisasi Etika Komunikasi sebagai Upaya Peningkatan Karakter Siswa di MA Ma’arif Cepogo - Fadina, Nesa Citra; Fadilla, Nayla Auline; Falah, Naufal Putra Nur; Safitri, Unna Ria; Chumaeson, Wahyuning (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This activity focuses on guiding the students of class X MA Ma'arif Cepogo in forming communication ethics in themselves. In addition, this activity aims to distribute information and knowledge about proper communication ethics, to improve the character of students at MA Ma'arif Cepogo. Through this community service activity, it is hoped that the students of class X MA Ma'arif Cepogo will get an idea of how to communicate well. The methods applied in this community service include direct socialization to students of class X MA Ma'arif Cepogo regarding communication ethics education in the school environment, with stages of introduction to the development of moral values in the school environment network, as well as the implementation of community service activities. This socialization event received a positive response from the school, especially the students, because it provided an understanding and knowledge related to good communication ethics in accordance with the school's vision in forming student characters who maintain norms of politeness and togetherness in interactions, as well as providing a positive influence on the school community as a whole.